1999
DOI: 10.1002/(sici)1097-010x(19990701)284:2<225::aid-jez12>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandins and reproduction of the scallop Argopecten purpuratus: I. relationship with gamete development

Abstract: In order to learn about factors that influence the reproductive cycle of marine bivalves, the levels of prostaglandins (PGs) PGE 2 and PGF 2α were measured during gametogenesis in the functional hermaphrodite scallop, Argopecten purpuratus. The PGs, in extracts of gonads of these scallops, were measured by radioimmunoassay techniques on different days after an induced spawning. To verify that gametogenesis was taking place during the experimental time, each time scallops were sampled, gonadal maturation was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…For instance, Knight et al (1999) Others, however, have taken it for granted that the product identified and quantified by EIA or RIA is only that defined by the assay (e.g. Hagar et al, 1989;Martínez et al, 1999;Tahara and Yano, 2003), despite the possibility of the presence of alternative fatty acid substrates in these animals. It must be remembered that the specificity of these assays totally depends on the antibodies used as well as the degree to which samples have been extracted prior to the assay.…”
Section: Table·1 Prostaglandin (Pg) Generation In Non-insectan Invermentioning
confidence: 99%
“…For instance, Knight et al (1999) Others, however, have taken it for granted that the product identified and quantified by EIA or RIA is only that defined by the assay (e.g. Hagar et al, 1989;Martínez et al, 1999;Tahara and Yano, 2003), despite the possibility of the presence of alternative fatty acid substrates in these animals. It must be remembered that the specificity of these assays totally depends on the antibodies used as well as the degree to which samples have been extracted prior to the assay.…”
Section: Table·1 Prostaglandin (Pg) Generation In Non-insectan Invermentioning
confidence: 99%
“…It has been demonstrated, both in vertebrates and invertebrates, that sperm glycosidases and glycosyltransferases are the first receptors for the carbohydrates of the egg surface in early gamete recognition (Martinez et al, 2000;Mengerink and Vacquier, 2001;Koyanagi and Honegger, 2003;Zitta et al, 2006;Lyng and Shur, 2007). It is known that several other proteins of the sperm surface, such as proteases, tyrosine kinases and phospholipases, may also function as receptors for the egg coat(s) in mammals (Mengerink and Vacquier, 2001;Wassarman et al, 2001;Miller and Pitnick, 2002;Talbot et al, 2003;Shur et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In the marine scallop A. purpuratus, the timing and duration of gonad maturation and spawning are under the control of various exogenous and endogenous factors. Martínez et al (1999Martínez et al ( , 2000 reported that the prostaglandins (PGE2 and PGF2) and the dopaminergic mechanisms, controlled by dopamine, noradrenaline, and serotonin (5-HT), play a major role in the spawning process and during gametogenesis. Recently, cyclic AMP has been shown to be involved in the regulation of reproductive processes via the phosphorylation of different kinds of proteins for each stage (Martínez and Cisterna, 2004).…”
Section: Introductionmentioning
confidence: 99%